MENTAL HEALTH, A CHALLENGE FOR MEN AND WOMEN (CIPEEX, 2024)
MENTAL HEALTH IS A STATE OF EMOTIONAL BALANCE THAT ENABLES INDIVIDUALS TO FACE LIFE'S CHALLENGES, COPE WITH STRESS, MAINTAIN HEALTHY RELATIONSHIPS, AND REALIZE THEIR POTENTIAL. FOR ADULTS, IT INVOLVES THE CAPACITY TO MANAGE PROFESSIONAL AND PERSONAL PRESSURES, MAINTAIN EMOTIONAL RESILIENCE IN THE FACE OF ADVERSITY, AND SEEK HELP WHEN NECESSARY. THE OBJECTIVE OF THIS STUDY IS TO ASSESS THE MENTAL HEALTH STATUS OF ADULTS, AIMING TO IDENTIFY SYMPTOMS AND FACTORS RELATED TO PSYCHOLOGICAL WELL-BEING. THE SELF-REPORTING QUESTIONNAIRE-20 (SRQ-20) WAS USED AS THE RESEARCH INSTRUMENT, PROVIDING AN ANALYSIS OF THE PHYSICAL, PSYCHOLOGICAL, SOCIAL, AND ENVIRONMENTAL DOMAINS OF THE RESPONDENTS. THE QUESTIONNAIRE WAS ADMINISTERED THROUGH GOOGLE FORMS, ONLINE VIA A LINK SENT THROUGH THE WHATSAPP APPLICATION TO MEN AND WOMEN OVER 18 YEARS OLD IN A MUNICIPALITY IN THE INTERIOR OF THE STATE OF GOIS, BRAZIL. THE RESEARCH RESULTS REVEALED A HIGH INCIDENCE OF SYMPTOMS SUCH AS HEADACHES, ANXIETY, FEAR, AND INSOMNIA, ALONG WITH POOR SLEEP QUALITY. THIS INDICATES THAT MANY PARTICIPANTS MAY BE EXPERIENCING DIFFICULTIES IN VARIOUS DIMENSIONS OF THEIR MENTAL HEALTH. FROM A PHYSICAL PERSPECTIVE, FREQUENT HEADACHES CAN BE INDICATIVE OF CHRONIC STRESS OR TENSION, WHILE INSOMNIA AND POOR SLEEP QUALITY CAN IMPAIR COGNITIVE AND EMOTIONAL FUNCTIONING. IN THE PSYCHOLOGICAL ASPECT, ANXIETY AND FEAR ARE SYMPTOMS ASSOCIATED WITH DISORDERS THAT CAN HAVE A SUBSTANTIAL IMPACT ON QUALITY OF LIFE. OTHER RESULTS SHOW THAT A SIGNIFICANT PORTION OF RESPONDENTS REPORTED BEING EASILY STARTLED, HAVING DIFFICULTY THINKING CLEARLY, FEELING SADNESS, STRUGGLING TO PERFORM DAILY ACTIVITIES WITH SATISFACTION, MAKING DECISIONS, EXPERIENCING CONSTANT FATIGUE, AND HAVING UNPLEASANT SENSATIONS IN THE STOMACH. THIS POINTS TO THE NEED FOR A MORE IN-DEPTH ASSESSMENT AND APPROPRIATE INTERVENTIONS TO ADDRESS THESE CHALLENGES. THESE SYMPTOMS MAY BE RELATED TO ANXIETY DISORDERS, DEPRESSION, CHRONIC STRESS, OR OTHER MENTAL HEALTH CONDITIONS. IN SUMMARY, THE RESULTS HIGHLIGHT THE NEED FOR A MORE COMPREHENSIVE AND PROACTIVE APPROACH TO MENTAL HEALTH. THIS INCLUDES PROMOTING AWARENESS, IMPLEMENTING PREVENTION STRATEGIES, RECOGNIZING THE INFLUENCE OF VARIOUS FACTORS, AND FACILITATING ACCESS TO MENTAL HEALTH SERVICES.
Keywords: Quality of Life; Mental Health; Psychological Well-being; SRQ-20